Rapid response teams to support dementia care in Australian aged care homes: Review of the evidence. (19th November 2019) - Westera, Anita; Fildes, David; Grootemaat, Pam; Gordon, Rob
Abstract: Objectives: To identify attributes of rapid response services designed to support people with very severe and extreme responsive behaviours, otherwise known as behavioural and psychological symptoms of dementia, in aged care homes. Methods: A rapid evidence assessment was conducted to inform the evaluation of the Severe Behaviour Response Team (SBRT) service, including a targeted search of peer‐reviewed academic literature and an Internet‐based search of government, service provider, peak body and university websites. Results: A number of localised rapid response services targeting people with similar clinical profiles were identified, but none operated on the scale of the SBRT. Five operational attributes in common were as follows: clearly defined parameters and processes; provision of clinical expertise and knowledge translation activities; person‐centred philosophy; relationship‐oriented approach to stakeholders; and generalisable and sustainable outcomes. Conclusions: The five attributes provided a useful framework to guide the evaluation of the SBRT and clarify opportunities for continued service development.